Analysis of the Preparation of the Regional Medium-Term Development Plan (RPJMD) of Minahasa Regency for the 2018-2023 Period - Steven V. Tarore,; Abdul R. Dilapanga,; Ulfa U. Azizah,; Laurens Bulo, (Technium Social Sciences Journal, 2023)
This study aims to explain the process of preparing the RPJMD in Minahasa Regency for the 2018-2023 period. In this study using a qualitative approach. The following research results are: 1) Preparation Cycle, the preparation of development plans is always based on the preparation and planning script and the planning cycle of development preparation provides convenience for Bappeltbangda, 2) Musrenbang activities, joint deliberation process After the initial draft of the RPJMD is refined and the draft of the PD Strategic Plan has been verified, then both are combined and become the draft of the RPJMD, 3) Planning and development, implementation of initial planning It has been systematically and the mechanism is based on the script system, there are inhibiting factors, namely discipline in SKPD data in evaluating their performance outcomes and outputs, lack of discipline and limited human resources.